Situation Report: Baltic Area, 7 June 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Differences in Curricula for Estonians and Russian Inhabitants of Estonia / by Toomas Ilves New Ideological Secretary / by Dzintra Bungs Imprisoned Dissident Asks to Emigrate from the USSR / by Dzintra Bungs The Pope's Benediction for Latvians and Estonians / by Dzintra Bungs The KGB's Efforts to Infiltrate the Lithuanian Seminary / by Saulius Girnius Soviet Accusations against Three Dissidents / by Saulius Girnius The Sixty-Fifth Issue of the Lithuanian Chronicle / by Jonas Papartis